Social Interaction on Children's Weddings in Rajek Dusun, Berang Village, Simpang Teritip District, West Bangka District - sulistiya dewi; Sulaiman, Aimie; Pasaribu, Waldimer (Strata International Journal of Social Issues, 2024)
This descriptive qualitative research explores the social interactions and underlying factors contributing to child marriage in Rajek Dusun, Berang Village, Simpang Teritip District. Child marriage, defined as marriage involving individuals under 16 for women and 19 for men, remains prevalent despite legal prohibitions. The study employs interviews and observations to gather data from individuals, objects, and entities that provide relevant information. Findings indicate that socio-economic pressures, cultural customs, and lack of awareness about legal and health implications drive child marriage. The research highlights the adverse outcomes of early marriage, particularly for young women who face increased risks to their reproductive and mental health. Community perspectives reveal that traditional norms often override legal measures, perpetuating the practice. The study underscores the need for comprehensive community education programs focusing on early marriage's legal, health, and social implications. Collaborative efforts between local government and community leaders are essential to raise awareness and support young individuals in their transition to adulthood. By prioritizing education, health services, and vocational training, the community can work towards reducing the incidence of child marriage and promoting healthier, more prosperous futures for its members.